Measurement of single low-density lipoprotein particles by atomic force microscopy. (November 2013) - Sakurai, Toshihiro; Takeda, Seiji; Takahashi, Jun-ya; Takahashi, Yuji; Wada, Norio; Trirongjitmoah, Suchin; Namita, Takeshi; Jin, Shigeki; Ikuta, Akiko; Furumaki, Hiroaki; Hui, Shu-Ping; Fuda, Hirotoshi; et al.
Background: The size of lipoprotein particles is relevant to the risk of coronary artery disease (CAD). Methods: We investigated the feasibility of atomic force microscopy (AFM) for evaluating the size of large low-density lipoprotein (LDL) and small dense LDL (sd-LDL) separated by ultracentrifugation. The measurements by AFM in tapping mode were compared to those by electron microscopy (EM). Results: There was a significant difference in particle sizes determined by AFM between large LDL (20.6 ± 1.9 nm, mean ± SD) and sd-LDL (16.2 ± 1.4 nm) obtained from six healthy volunteers ( P < 0.05). The particle sizes determined by EM for the same samples were 23.2 ± 1.4 nm for large LDL and 20.4 ± 1.4 nm for sd-LDL. The difference between large LDL and sd-LDL detected by EM was also statistically significant ( P < 0.05). In addition, the particle sizes of each lipoprotein fraction were significantly different between AFM and EM: P < 0.05 for large LDL and P < 0.05 for sd-LDL. Conclusions: AFM can differentiate between sd-LDL and large LDL particles by their size, and might be useful for evaluating risk for CAD.